Transforming and Grappling with Concepts of Activism and Feminism with Indigenous Women Artists - Nagam, Julie (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
This essay reflects on the multiple relations between the socially constructed terms of activism, feminism and Indigenous artists and whether such reflections connect to a larger discussion surrounding colonization, hegemonic western art practices and the lack of female Indigenous artists in the mainstream art world.